1969
DOI: 10.1007/bf00427976
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of different organs and tissues of the rat to assimilation of glucose

Abstract: After intravenous injection of glucose, 750 mg/kg, together with a tracer dose of [U-14C] glucose, into fasted, adult white rats, the following percentages of the administered dose were found in whole organs and tissues : 1. after five minutes : skeletal muscle 30.3, skin 28.1, blood 13.1, adipose tissue 10.7, liver 8.9. 2. Forty minutes after injection the corresponding values were: 35.0, 11.1, 5.0, 4.6 and 9.4%. Expired 1~CO~ was negligible after five minutes: after 40 min it comprised 8% of the total dose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 10 publications
3
20
0
Order By: Relevance
“…On a weight basis, skeletal muscle is the most important glucose-utilizing tissue [11]. In man, it has been demonstrated that skeletal muscles are primarily responsible for the disposal of an intravenous glucose toad in an euglycaemic clamp [12].…”
Section: Discussionmentioning
confidence: 99%
“…On a weight basis, skeletal muscle is the most important glucose-utilizing tissue [11]. In man, it has been demonstrated that skeletal muscles are primarily responsible for the disposal of an intravenous glucose toad in an euglycaemic clamp [12].…”
Section: Discussionmentioning
confidence: 99%
“…4 B) again confirmed that the insulin-stimulated glycogen repletion was severely impaired in diabetic rats and was completely restored to normal by the treatment with vanadate, but not with phlorizin. Because muscle mass in the rat represents 40% of the body weight (43,45), it is possible to calculate the contribution of skeletal muscle glycogen synthesis to the whole body glucose uptake. In normal rats (group 1), 35% of the tissue glucose uptake (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The whole body muscle glycogenic rates displayed in this figure are obtained from the data shown in Fig. 4 B assuming that total body muscle mass in the rat is 40% of the body weight (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscles are important targets for insulin, since they are the major insulin-dependent peripheral tissue in the body. They represent 40 -50% of total body weight and contribute to 35% of glucose uptake in response to an intravenous glucose injection (33). Increased muscle weight and decreased fat depot weight probably contribute to the increased sensitivity to insulin and increased muscle glucose uptake in LPS-treated rats.…”
Section: Control Lpsmentioning
confidence: 99%